Calcined Clay in Dry Deep Mixing - Kristiansson Högefjord, William; Wedholm, Tobias (My University, 2024)
Dry deep mixing is a common form of ground improvement in the Nordic countries. With the increasing strive to reduce carbon emissions, smart solutions are frequently needed. This thesis presents a new type of binder mixture containing calcined clay. The proposed binder mixtures were combined with a wet silty-clay found in the northern parts of Gothenburg. The binders have been subjected to a standardised UCS-test from which the local secant stiffness (E50) and unconfined compressive strength were derived. Data from the laboratory test was compiled and compared against requirements obtained from a finite element analysis. The model was constructed in compliance with Trafikverket’s regulations. One of the proposed new binders which contained 80 % lime and 20 % calcined clay surpassed the set criteria after 28 days of curing. The achieved unconfined compressive strength was approximately 200 kPa and 100 MPa for the local secant stiffness. Furthermore, the potential emission reduction with the proposed binder was calculated to 11 % when 80 kg binder m3 clay was used when compared to a traditional lime-cement mixture. However, the new binder is still in an early testing phase which is associated with large uncertainties, namely the variance in results. In conclusion, while promising, further research will be crucial to fully assess the long-term performance and environmental impact of the proposed binder mixture.
Keywords: Dry deep mixing; Calcined Clay; UCS-test; local secant stiffness; Finite element analysis; Carbon Dioxide Emission